Kajian Jenis Media Simpan Terhadap Mutu Pisang Cavendish (Musa parasidiaca ‘Cavendish’) - Ifmalinda Ifmalinda; Riska Westri Windasari (Department of Agricultural Engineering, Syiah Kuala University, 2018)
Abstrak. Pisang Cavendish merupakan salah satu jenis pisang yang cukup potensial dan banyak dikonsumsi oleh masyarakat, baik untuk olahan maupun untuk santapan segar. Pisang merupakan buah klimakterik yang tetap mengalami proses kematangan walaupun telah dipanen dan diikuti dengan proses kerusakan karena buah tetap melangsungkan proses respirasi dan metabolisme (Sumadi, et al., 2004). Hal ini merupakan kendala dalam upaya memperpanjang umur simpan buah pisang Cavendish. Cara mengatasi permasalahan tersebut yaitu dengan melakukan perbaikan penanganan pascapanen, agar kualitasnya dapat dipertahankan setelah panen dilakukan. Pelilinan dan pemilihan media simpan merupakan salah satu teknologi pascapanen dalam mempertahankan mutu produk yang berfungsi mengurangi kerusakan produk pertanian akibat proses respirasi. Tujuan dilakukannya penelitian ini adalah untuk mengkaji pengaruh media simpan berupa pasir dan serbuk gergaji terhadap mutu dan umur simpan pisang yang telah dilapisi lilin selama penyimpanan. Pemberian jenis media simpan selama penyimpanan buah pisang berpengaruh terhadap mutu pisang yaitu nilai kerusakan mekanis, susut bobot, TPT, hue, kekerasan dan kadar air buah pisang selama penyimpanan. Umur simpan buah pisang yang terlama terdapat pada perlakuan ada pemberian media simpan serbuk gergaji (A0M1) dengan 15 hari umur simpan. Study Media Types Storage on Cavendish Banana Quality (Musa parasidiaca ‘Cavendish’) Abstract. Cavendish banana is one type of banana is quite potential and widely consumed by the community, both for processing and for fresh cuisine. Banana is a climacteric fruit that continues to experience the process of maturity although it has been harvested and followed by the destruction process because the fruit continues the process of respiration and metabolism (Sumadi, et al., 2004). This is an obstacle in an effort to extend the life of the Cavendish banana shelf. How to overcome these problems is to make improvements postharvest handling, so that quality can be maintained after harvest is done. Pelilinan and the selection of media store is one of the postharvest technology in maintaining product quality that serves to reduce the damage of agricultural products due to respiration process. The purpose of this research is to examine the effect of storage media in the form of sand and sawdust on the quality and life of banana shelf that has been coated wax during storage. Giving the type of storage media during the storage of bananas affect the quality of bananas are the value of mechanical damage, weight loss, TPT, hue, hardness and moisture content of bananas during storage. The oldest banana-saving age was found in the treatment of sawdust storage media (A0M1) with 15 days of shelf life. fermentation box to the environment in the outside. The results showed that the ideal temperature of fermentation in wooden boxes was obtained in the fifth day, while the ideal temperature of fermentation in Styrofoam was obtained in the third day. Heat transfer in the wood material is higher than in the Styrofoam material. This was due of the heat in a wooden box go out faster, so that the temperature in the fermentation process may be lower than using a Styrofoam box. The result of cocoa seed fermentation using a wooden box obtained a good cocoa seed on the fifth day of fermentation and while using a Styrofoam box cocoa seed were moldy in the fifth day.